Fetal Alcohol Exposure Alters Blood Flow and Neurological Responses to Transient Cerebral Ischemia in Adult Mice. (17th December 2016) - Bake, Shameena; Gardner, Rachel; Tingling, Joseph D.; Miranda, Rajesh C.; Sohrabji, Farida
Abstract : Background: Prenatal alcohol exposure (PAE) can result in physical and neurocognitive deficits that are collectively termed "fetal alcohol spectrum disorders" (FASD). Although FASD is associated with lifelong intellectual disability, the mechanisms mediating the emergence of secondary mental health and physical disabilities are poorly understood. Based on our previous data showing that maternal ethanol (EtOH) exposure in mice resulted in an immediate reduction in cranially directed fetal blood flow, we hypothesized that such exposure would also result in persistent alterations in cranially directed blood flow in the prenatally alcohol‐exposed (PAE) adult. We also hypothesized that PAE adults exposed to an acute cerebrovascular insult would exhibit more brain damage and neurobehavioral impairment compared to non‐PAE adult controls. Methods: Pregnant C57BL/6 mice were exposed to EtOH, 3 g/kg, or water by intragastric gavage. Blood flow in carotid, renal, and femoral arteries was assessed by ultrasound imaging in PAE and control adults at 3, 6, and 12 months of age. To mimic ischemic stroke in young adult populations, 3‐month‐old PAE and control animals were subject to transient middle cerebral artery occlusion (MCAo) and subsequently assessed for behavioral recovery, stroke infarct volume, and brain cytokine profiles. Results: PAE resulted in a significant age‐related decrease in blood acceleration in adult mice, specifically in the carotid artery. A unilateral transient MCAo resulted in equivalent cortico‐striatal damage in both PAE and control adults. However, PAE adult mice exhibited significantly decreased poststroke behavioral recovery compared to controls. Conclusions: Our data collectively show that PAE adult mice exhibit a persistent, long‐term loss of cranially directed blood flow, and decreased capacity to compensate for brain trauma due to acute‐onset adult diseases like ischemic stroke. Abstract : Our study assessed long‐term consequences of prenatal alcohol exposure (PAE) on blood flow and on behavioral outcomes following unilateral middle cerebral artery occlusion (MCAo)‐induced transient ischemic stroke in adults. PAE resulted in a significant age‐related decrease in blood acceleration in mature adult and middle‐aged mice, specifically in the carotid artery. Following MCAo, adult PAE mice exhibited significantly decreased behavioral recovery compared with controls. Therefore, PAE results in impaired cranially directed blood flow and poor stroke outcomes in the adult.